The Kufan Qurra' in early Islam. - Mahayudin Haji Yahaya (Universiti Kebangsaan Malaysia, 1980)
The conquest of Iraq served not only to force a new geographical strategy on the Arab military forces but at the same time to change the social and economic life of the Arab conquerors. The enormous wealth, particularly land and property acquired by the conquest during 'Umar b. al-Khattab's caliphate were together one of the most important reasons for Arab settlement in the town of Kufa. This also became the vital issue in the study of the qurra' and from whose ranks the Khawarij belonged. This paper attempts to establish a link between the disputes over some of the occupied territories in the Sawad (Iraq) and the emergence of the qurra' and the Khawarij respectively. It also attempts to redefine the qurra' according to the early Arab sources.